Education on Balanced Nutrition and Healthy Canteens in Early Childhood Education and Kindergarten at Baitul Qur'an Islamic Boarding School for Children - Amilia Yuni Damayanti; Ayu Suryaningtyas Sabastiani; Aziza Nurul Masruroh; Syadza Syafa Nazhifah; Jihan Fauziyah Salsabila (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Balanced nutrition and a healthy canteen have an important role in maintaining public health, especially for children. Currently, people tend to live pragmatically, including the choice of instant food which can hurt health in the future. The prevalence of stunting and nutritional problems in children is still a serious problem in Indonesia. The knowledge of mothers and socio-economic factors have an important role in nutritional problems for children. Therefore, education about balanced nutrition and healthy canteens is important to increase public knowledge and behavior. The results of this community service activity show a significant increase in the understanding of balanced nutrition among student parents. Although improvements have been made, ongoing efforts are needed to ensure this understanding is maintained. This activity also motivates schools to set up healthy canteens as an alternative solution to a healthier diet for children.